Learning Malaysian Sign Language with AR - Nur Basirah Ayob Ali; Nurin Batrisya Bohanuddin; Wan Nur Amni Humaira Wan Mohd Nasrudin; Berahim, Mazniha (Multidisciplinary Applied Research and Innovation, 2025)
This project investigates the potential of Augmented Reality (AR) to enhance independent learning of Malaysian Sign Language (MSL). Traditional methods often require teacher assistance, making self- learning challenging. This project explores AR as a solution, aiming to create a more interactive and engaging experience. A user-centered design methodology approach was employed throughout the project, adhering to the Multimedia Development Life Cycle (MDLC) framework. This ensured the AR application catered specifically to the needs and preferences of MSL learners. The development process followed the MDLC framework, encompassing stages from concept, design, material collecting, assembly to testing, and distribution. Unity was chosen as the platform for the AR application due to its capabilities in integrating 3D elements and interactive features. The resulting AR application utilizes 3D hand models and interactive quizzes. These features enable users to visualize and practice MSL signs in a more immersive and effective manner. Additionally, a companion MSL book (focusing on days and months) was created to complement the AR application. This bridges the gap between physical and digital learning resources. This combined approach aims to improve the accessibility and effectiveness of MSL education. The project emphasizes the potential of AR in educational contexts and highlights the importance of user-centered design. Future work can expand the content library and ensure broader device compatibility, further maximizing accessibility and paving the way for AR as a valuable tool for MSL learning.